Christmas books for children - Giddens, Eugene ca. 20./21. Jh (Cambridge elements, 2019)
This Element traces the varied and magical history of Christmas publications for children. The Christmas book market has played an important role in the growth of children's literature, from well-loved classics to more ephemeral annuals and gift books. Starting with the eighteenth century and continuing to recent sales successes and picturebooks, Christmas Books for Children investigates continuities and new trends in this hugely significant part of the children's book market